STORYTELLING SEBAGAI TEKNIK PEMBELAJARAN PENGEMBANGAN KARAKTER DIRI ANAK DI RUMAH BELAJAR CAHAYA INDONESIA - Wida Nofiasari; Carli Apriansyah Hutagalung (Jurnal Abdimas Bina Bangsa, 2023)
This Community Service is an activity carried out to build children's character from an early age through learning techniques using storytelling. The partner for this activity is the children at the Cahaya Indonesia Learning Center in Kedaung Wetan neighborhood, Neglasari District, Tangerang City, Banten Province, whose students are children aged 6 to 11 years old. There are 30 children involved in this activity, which was held on December 18, 2022. The aim of this community service is to support formal education in shaping children's characters from an early age so can express themselves, tell stories, communicate, and contribute well to the progress of the nation. The learning technique used include showing animation videos, storytelling techniques, discussion methods, and simulation methods. The success rate is measured through observation by looking at the enthusiasm of the children in participating in the community service program and the number of children present. The achieved results of the community service are that the use of storytelling techniques in the learning process is quite effective in facilitating children's learning in shaping their characters with good habits and helping children to think creatively, adaptively, and competitively